2017
DOI: 10.1117/12.2265670
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic measurements of physical quantities in extreme environment using fiber Bragg grating

Abstract: Fiber Bragg Gratings (FBGs) are used to measure shock velocity, detonation velocity, shock wave profile or pressure profile in inert and energetic materials. Such thin probe, with a diameter below 150 µm, can be inserted directly into materials without disturbing the physical phenomena. Chirped FBGs are used to track the shock wave in the grating using wavelengths. The velocity (few km/s) and shock wave profile measurements are realized by recording the CFBG's reflected spectral width. Pressure measurements at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…It makes use of a Luna OBR 4600 equipment and has the advantages of being non-destructive, fast, and accurate in the space domain (0.01 mm). In return, the spatial uncertainty is conditioned by the uncertainty concerning the value of the effective index neff of the guided mode, France (CEA), Israel (NRC Soreq), China (BUAA), and England (AWE + ORC Southampton) reported results [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] over the last two decades. The measurement principle remains the following: a CFBG is either placed along or even inside an HE material as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It makes use of a Luna OBR 4600 equipment and has the advantages of being non-destructive, fast, and accurate in the space domain (0.01 mm). In return, the spatial uncertainty is conditioned by the uncertainty concerning the value of the effective index neff of the guided mode, France (CEA), Israel (NRC Soreq), China (BUAA), and England (AWE + ORC Southampton) reported results [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] over the last two decades. The measurement principle remains the following: a CFBG is either placed along or even inside an HE material as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Different HE material experimental configurations were tested at CEA Gramat and at CRB (Centre de Recherche du Bouchet, ArianeGoup) over the last decade [9,12,[14][15][16][17]25]. New experimental results, with uncertainty calculations, are presented in Section 6 of this paper: bare cylinder, wedges for shock-to-detonation transitions, and sphere configurations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor placed in this way enables the shockwaves to be traced inside the material using the Bragg wavelength. In this application, the speed (several km/s) and measurements of the shockwave profile are carried out by recording the reflected spectrum from the CFBG [4].…”
Section: Introductionmentioning
confidence: 99%
“…Once they have been used solely in wavelength-division multiplexed communication networks [1,2]. In the course of time, their spectacular characteristics have expanded their application domain to spectroscopy and chemical sensors [3][4][5][6][7]. Many research groups have reported implementation of the AWGs on various platforms, such as silicon-on-insulator, silica-on-silicon and silicon-based polymers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%